2015
DOI: 10.1002/jsfa.7441
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of salmon (Salmo salar L.) protein fraction hydrolysates revealed following their ex vivo digestion and in vitro hydrolysis

Abstract: The results indicate the salmon myofibrillar and sarcoplasmic protein fractions as potential sources of antioxidant peptides that could be released in the gastrointestinal tract but their amino acid sequence and quantification vary. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 51 publications
1
17
0
2
Order By: Relevance
“…The reducing power of Rv hydrolysates exhibited the similar digestive characteristics to the DPPH radical scavenging activity that the simulated GI digestion decreased the reducing power of hydrolysates. Though, many research reported that the GI digestion improved the reducing power of food resources such as salmon protein (Borawska et al ., ), a similar trend as in our study was also reported for Cape hake by‐products (Teixeira et al ., ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The reducing power of Rv hydrolysates exhibited the similar digestive characteristics to the DPPH radical scavenging activity that the simulated GI digestion decreased the reducing power of hydrolysates. Though, many research reported that the GI digestion improved the reducing power of food resources such as salmon protein (Borawska et al ., ), a similar trend as in our study was also reported for Cape hake by‐products (Teixeira et al ., ).…”
Section: Resultssupporting
confidence: 92%
“…It is interesting to note that the simulated GI digestion decreased the DPPH scavenging activity when compared to the undigested samples ( P < 0.05). Though, many research reported the GI digestion improved the DPPH scavenging activity of food resources, a similar trend was also reported for salmon (Borawska et al ., ) and carp (Borawska et al ., ). Unlike Rv visceral mass, intestinal digestion slightly but significantly ( P < 0.05) improved the DPPH radical scavenging activity of Rv meat compared to the gastric digestion.…”
Section: Resultsmentioning
confidence: 99%
“… 29 , 30 These vascular antagonistic actions with Ang II could also be helped by its free radical reducing and scavenging ability, 30 which can be related to the very hydrophobic nature of its molecular moiety. 31 Interestingly, Ang-(3−4) is effective when administered orally, 26 , 32 , 33 a property associated with its resistance to hydrolysis and its high capacity to permeate intestinal cells. 34 One mechanism proposed to explain these effects involves l -type Ca 2+ channels, independently of Ang II receptors.…”
Section: Angiotensin-(3−4)mentioning
confidence: 99%
“…Así mismo, se favoreció la capacidad de reducción del ion Fe +3 , tanto para la fracción globular sin hidrolizar como para sus hidrolizados a diferentes tiempos de hidrolisis, posiblemente porque durante el proceso de digestión in vitro se liberan péptidos con capacidad antioxidante (Zhu et al, 2008;Borawska et al, 2016).…”
Section: Capacidad Antioxidanteunclassified